2017
DOI: 10.1128/aac.01343-16
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Emergence of Genetically Resistant Mutants of Mycobacterium tuberculosis from the Persistence Phase Cells Formed against Antituberculosis Drugs In Vitro

Abstract: Bacterial persisters are a subpopulation of cells that can tolerate lethal concentrations of antibiotics. However, the possibility of the emergence of genetically resistant mutants from antibiotic persister cell populations, upon continued exposure to lethal concentrations of antibiotics, remained unexplored. In the present study, we found that Mycobacterium tuberculosis cells exposed continuously to lethal concentrations of rifampin (RIF) or moxifloxacin (MXF) for prolonged durations showed killing, RIF/MXF p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
142
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 105 publications
(158 citation statements)
references
References 112 publications
(171 reference statements)
10
142
0
Order By: Relevance
“…Background information and experimental strategy. We had earlier found that M. tuberculosis (Mtb) and M. smegmatis (Msm) cells, which were exposed to minimum bactericidal concentrations (MBCs) of rifampicin and moxifloxacin for prolonged duration in vitro such as 18 days for Mtb cells and 96 hrs for Msm cells, showed a sequential killing, persistence and regrowth phases (Sebastian et al, 2017;Swaminath, 2017). In these studies, rifampicin-resistant and moxifloxacin-resistant genetic mutants of Mtb and Msm were found to emerge from the persister population, regrow and populate the culture.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Background information and experimental strategy. We had earlier found that M. tuberculosis (Mtb) and M. smegmatis (Msm) cells, which were exposed to minimum bactericidal concentrations (MBCs) of rifampicin and moxifloxacin for prolonged duration in vitro such as 18 days for Mtb cells and 96 hrs for Msm cells, showed a sequential killing, persistence and regrowth phases (Sebastian et al, 2017;Swaminath, 2017). In these studies, rifampicin-resistant and moxifloxacin-resistant genetic mutants of Mtb and Msm were found to emerge from the persister population, regrow and populate the culture.…”
Section: Resultsmentioning
confidence: 99%
“…Bacteria, both pathogenic and non-pathogenic, of diverse genera and habitat have shown the phenomenon of persistence. With mycobacteria being no exception to this trait, large number of studies have been carried out on Mycobacterium tuberculosis persisters McCune et al, 1966a, b;Hu et al, 2000;Lenaerts et al, 2007;Hoff et al, 2011;Sebastian et al, 2017). High density of acidfast bacilli has been found in the tubercles resected months after the patients on chemotherapy had become sputum negative (Medlar et al, 1952;Beck and Yegian, 1952).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations